2010
DOI: 10.1124/dmd.110.035048
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Stability-Dependent Circulation of Acyl Glucuronide Metabolites in Humans: How Circulating Metabolite Profiles of Muraglitazar and Peliglitazar Can Lead to Misleading Risk Assessment

Abstract: ABSTRACT:Muraglitazar and peliglitazar, two structural analogs differing by a methyl group, are dual peroxisome proliferator-activated receptor-␣/␥ activators. Both compounds were extensively metabolized in humans through acyl glucuronidation to form 1-O-␤-acyl glucuronide (AG) metabolites as the major drug-related components in bile, representing at least 15 to 16% of the dose after oral administration. Peliglitazar AG was the major circulating metabolite, whereas muraglitazar AG was a very minor circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…Since DF-AG is chemically unstable, and prone to back-conversion to DF, transportermediated DDIs involving DF-AG could complicate the plasma exposure of parent DF. It is worth noting that acidification of plasma samples is a critical requirement to protect DF-AG from degradation and accurately determine the systemic exposure of DF-AG (Zhang et al, 2011). The findings in the current investigation have revealed the possibility for greater numbers of transporters involved in DF-AG disposition, and raise concerns regarding possible DDI with DF-AG.…”
Section: Discussionmentioning
confidence: 80%
“…Since DF-AG is chemically unstable, and prone to back-conversion to DF, transportermediated DDIs involving DF-AG could complicate the plasma exposure of parent DF. It is worth noting that acidification of plasma samples is a critical requirement to protect DF-AG from degradation and accurately determine the systemic exposure of DF-AG (Zhang et al, 2011). The findings in the current investigation have revealed the possibility for greater numbers of transporters involved in DF-AG disposition, and raise concerns regarding possible DDI with DF-AG.…”
Section: Discussionmentioning
confidence: 80%
“…It is interesting to note that CYP2C8 has also been shown to metabolize estradiol-17␤-glucuronide to its 2-hydroxy analog (Delaforge et al, 2005). When oxidative metabolism of muraglitazar acyl glucuronide and peliglitazar acyl glucuronide was investigated in human liver microsomes fortified with NADPH, multiple oxidative metabolites of the glucuronide reference standards were observed (Zhang et al, 2011). Rates of metabolism in this study were comparable for both the acyl glucuronides.…”
Section: Glucuronides Undergoing Subsequent Oxidative Metabolismmentioning
confidence: 96%
“…This result indicated that there was very little plasma protein covalent binding, and the acyl glucuronide of peliglitazar was relatively stable in samples acidified immediately after collection and stored at Ϫ20°C. Other experiments to look at the stability of peliglitazar glucuronide were also performed, and the results are reported separately (Zhang et al, 2010).…”
Section: Downloaded Frommentioning
confidence: 99%